The Relationship Between Nutritional Status and Child Development Among Children Aged 2–5 Years at Puskesmas Seyegan - Monica Dwi Putri; Nidatul Khofiyah (Midwifery Department, Poltekkes Kemenkes Denpasar, Indonesia, 2026)
Developmental disorders in toddlers remain a global concern, particularly in developing countries such as Indonesia. Nutritional problems increase the risk of developmental delay by up to 4.75 times. Data from the Sleman District Health Office (2024) reported that 5.2% of toddlers in the working area of the Puskesmas Seyegan experienced nutritional problems and had never undergone developmental screening. This study aimed to determine the relationship between nutritional status and child development among children aged 2–5 years in this area. This quantitative descriptive study used an analytic cross-sectional design, involving 103 samples selected from a population of 1.581 toddlers using the Slovin formula, recorded in December 2025. Primary data were collected through anthropometric measurements (weight and height) to assess nutritional status and developmental screening using the KPSP instrument. Data were analyzed using univariate and bivariate analyses with the Spearman rank correlation test. The results showed a p-value < 0.001 (p < 0.05), indicating a significant relationship between nutritional status and child development. Most toddlers with normal nutritional status had normal development (84.9%), while those with abnormal nutritional status were more likely to experience doubtful (41.2%) and deviant development (11.8%). In conclusion, nutritional status is significantly associated with toddler development.